Assessment of SMC Frames under Different Column Removal Scenarios - Mariam Mohammed Ehab; Mina Mokhtar Maxi (Salehan Institute of Higher Education, 2020)
Throughout the past decades, failure of structures threatening the lives of humans had been popular whether through structure failure due to human error such as Hyatt Regency walkway collapse, 1981, terrorist attacks on the American embassy attack in Nairobi, Kenya 1998 and the famous 9/11 attacks in 2001 and many more. As a result of these incidents, The Unified Facilities Criteria (UFC) was developed concerning the progressive collapse issues by analyzing different types of structures under column loss and studying the overall structural behavior. However, the (UFC) didn’t scope on the local behavior of the structural components and its connection under column loss. In this research, the main objective is to study the local behavior of the special moment frame connection (SMC) under column loss. A detailed study is conducted on a 3D model fully designed by adopting the strong-column weak-beam approach following the ACI318-14 regulations. Two frames are selected from the designed structure, interior and exterior frames, to apply the column loss scenario in different locations and different floor levels. The Applied Element Method is adopted in the study. Non-linear time-dependent dynamic analysis is implemented to apply the different column removal scenarios. Twelve case studies are modeled in detail using the Extreme Loading for Structures (ELS) software at which all elements are modeled and analyzed in a 3D model technique. After analyzing the different case studies, structure behavior is observed. Some cases encountered total collapse, other cases encountered partial /local collapse and finally, some survived the column loss scenario. Many parameters are involved and studied in the research. Failure pattern is observed for collapsed cases, the cause of failure is monitored and studied. Special moment connection behavior is studied concerning the shear connection capacity. The location of the column removal with the type of frame selected played an important role in changing the structural behavior from one case to another. As a result, it is not applicable to assume that due to the special moment connection ductility, the structure will be able to resist the column loss in all cases.